Implementation of early will directives: facilities and difficulties experienced by palliative care teams - Aline Carniato Dalle Nogario; Edison Luiz Devos Barlem; Jamila Geri Tomaschewski-Barlem; Rosemary Silva da Silveira; Silvana Bastos Cogo; Deciane Pintanela de Carvalho
ABSTRACT Objective: To know the facilities and difficulties the palliative care team professionals experience in the implementation process of advance healthcare directives. Method: Exploratory-descriptive study with a qualitative approach, involving 51 professionals from seven palliative care teams in the state of Rio Grande do Sul, Brazil. The data were collected between December 2018 and April 2019 and discursive textual analysis was applied. Results: The facilities found were: the approach by the palliative care team; listening and respecting patients' wishes; effective communication between professionals, patients, and family members and resolution of difficult situations. The difficulties reported were: legal issues; the lack of knowledge of professionals about the subject; the lack of institutional protocols; the difficulty in talking about death and the family barrier. Conclusion: Despite the perceived facilities and difficulties, palliative care professionals intend to work based on the patients' desires and will, aiming to offer dignity in the dying process.